Russia and China national youth volleyball teams: injury data analysis on gender- and age- specific basis - Yun, H.; Bulykina, L. V.; Guba, V. P. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to analyze the gender- and age-specific injury statistics of the China and Russia national youth volleyball teams and develop injury prevention recommendations.